THE TRANSITION FROM INDUSTRIAL CAPITALISM TO A FINANCIALIZED BUBBLE ECONOMY. (1st April 2010) - Unknown
Abstract : For the past decade the US economy has been driven not by industrial investment but by a real estate bubble. As the economy's largest asset category, real estate generates most of the economy's capital gains. The gains are the aim of real investors, as the real estate sector normally operates without declaring any profit. Investors agree to pay their net rental income to their mortgage banker, hoping to sell the property at a capital gain (mainly a land-price gain). The tax system encourages this debt pyramiding. Tax favoritism to real estate—and behind it, to bankers as mortgage lenders—has spurred a shift of US investment away from industry toward speculation, mainly in real estate but also the stock and bond markets. A post-industrial economy is thus largely a financialized economy that carries its debt burden by borrowing against capital gains to pay the interest and taxes falling due.